Amirya, M. Dan Atmini, S. 2007. Pengaruh Motivasi Kerja, Konflik Peran, Dan Kepuasan Kerja Terhadap Kinerja Guru Di Smp Bahrul Maghfiroh Malang - Bambang Septiawan (Universitas Islam Balitar, 2016)
Teachers can perform well to accomplish their works influnced byhigh motivation and work satisfaction as well as minimun task conflictoccured. This research is aimed to investigate the influence of workmotivation, task conflict, and work satisfaction toward teachers workingperformance simultaneously as well as partially. This research location isat SMP Bahrul Maghfiroh Malang. Respondents of this research aretheachers of the school totally 17 teachers. Data is taken fromquestionnaire which is separated and filled by the teachers. Then thecollected data are analyzed by using SPSS tool(F test and T test) andinterpreted by the researcher. The result of this research proves that first,work motivation, task conflict, and work satisfaction influencesimultaneously teachers working performance significantly. Second, workmotivation influences partially working performance significantly. Third,task conflict influences partially working performance significantly. Fourth,work satisfaction influences partially working performance significantly.